Ruby the red fairy - Meadows, Daisy (Scholastic, 2003)
Friends Rachel and Kirsty, vacationing with their parents on Rainspell Island, go looking for the pot of gold at the end of the rainbow and instead find Ruby, one of the rainbow fairies who have been banished from Fairyland by Jack Frost, and promise to help unite all seven sisters and restore color to their world.